Evaluasi Kemampuan HCl dan H2SO4 Sebagai Aktivator Adsorben Bubuk Kulit Batang Sagu (Metroxylon Sagu) - Mukhlis .; Itnawita .; Ayu Chandra Kartika; Fika Filia Cani (Sistem Informasi, 2021)
Sago stem bark powder (Metroxylon sago) has the potential as an adsorbent because it contains cellulose, hemicellulose, and lignin. This study`s purpose was to determine the ability of the chemical activator in the hydrochloric acid and sulfuric acid to improve the adsorbent quality of sago stem bark powder according to SNI 06-3730-1995 standards. The method used is the bath system, where the sago stem bark powder is activated by soaking with HCl and H2SO4 for 24 hours using a variation of the adsorbent ratio and activator weight 1: 1, 1: 2, and 1: 3. The analysis was tested through characterization including moisture content, ash content, iodine absorption, and methylene blue absorption, as well as functional groups. From the research results, it was found that the two activators showed an optimal ratio of 1: 2 to provide optimal conditions for moisture content, ash content, iodine and methylene blue adsorption, surface area each of 1.64%; 3.14%; 261.41 mg/g; 4.80 mg/g; 17.76 m2/g for HCl activator and 2.67%; 3.20%; 261.10 mg/g; 4.79 mg/g; 17.67 m2/g for H2SO4 activator. From it this study can be concluded that the use of HCl and H2SO4 solutions did not show a significant difference as an activator to improve the quality of the sago stem bark powder adsorbent, the absorption value of iodine and methylene blue both activators have not been able to make sago stem bark powder as an adsorbent according to SNI 06-3730-1995 standards.